2021
DOI: 10.1097/md.0000000000024998
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of arthroscopic vs open ankle arthrodesis for advanced ankle arthritis

Abstract: Background: Ankle fusion is the primary treatment for advanced ankle arthritis. With the advancement of arthroscopy technology, ankle arthroscopy fusion has shown many advantages over traditional surgery. However, there are few related studies globally, and evidence-based medicine is needed to verify the reliability and feasibility of ankle arthroscopy fusion. Objective: To compare the clinical efficacy and safety of arthroscopic ankle arthrodesis and open ankle arthrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…A meta-analysis performed in 2021 found that patients undergoing arthroscopic ankle arthrodesis for the treatment of advanced tibiotalar osteoarthritis experienced a greater fusion rate, lower fusion time, lower intraoperative blood loss, decreased hospital length of stay, and an overall lower rate of postoperative complications when compared to those undergoing open surgery. 45 In addition, a separate meta-analysis performed in 2022 comparing outcomes of arthroscopic versus open Brostrom repair showed significantly less time to weight-bearing and decreased pain scores in the arthroscopic groups. 24 Perhaps the use of ankle arthroscopy within academic settings will rise overtime as the evidence supporting its indications continue to grow.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis performed in 2021 found that patients undergoing arthroscopic ankle arthrodesis for the treatment of advanced tibiotalar osteoarthritis experienced a greater fusion rate, lower fusion time, lower intraoperative blood loss, decreased hospital length of stay, and an overall lower rate of postoperative complications when compared to those undergoing open surgery. 45 In addition, a separate meta-analysis performed in 2022 comparing outcomes of arthroscopic versus open Brostrom repair showed significantly less time to weight-bearing and decreased pain scores in the arthroscopic groups. 24 Perhaps the use of ankle arthroscopy within academic settings will rise overtime as the evidence supporting its indications continue to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Second, placement of a long intramedullary nail in the subtalar joint via a plantar approach was an option. However, we consider it important to preserve an intact and flexible subtalar joint in a patient undergoing ankle arthrodesis in view of the study by Bai et al demonstrating that patients lose 74% of sagittal range of motion, 70% of rotational range of motion, and 77% of valgus range of motion after ankle fusion [35] . Third, there was a slight amount of residual lateral shift of the talus relative to the longitudinal axis of the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that arthroscopic ankle arthrodesis (AAA) results in higher fusion rates, less blood loss, shorter tourniquet time, and shorter hospital stay compared to open ankle fusion. 3,25 Although many consider AAA superior to open fusion, reported complications of AAA include nonunion, malunion, delayed wound healing, and infection. Of these, nonunion is recognized as one of the most important 1171077F AIXXX10.1177/10711007231171077Foot & Ankle InternationalWoods et al research-article2023 1 Nuffield Orthopaedic Centre, Oxford, UK 2 Horton General Hospital, Banbury, UK complications, with rates of 8% to 13% reported in systematic reviews.…”
Section: Introductionmentioning
confidence: 99%